Glycosidase-catalysed oligosaccharide synthesis: preparation of N-acetylchitooligosaccharides using the β- N-acetylhexosaminidase of Aspergillus oryzae - Singh, Suddham; Packwood, John; Samuel, Christopher J.; Critchley, P.; Crout, David H.G. (Carbohydrate research, 1995)
The β- N-acetylhexosaminidase of Aspergillus oryzae catalyses the formation of 2-acetamido-4- O-(2-acetamido-2-deoxy- β-d-glucopyranosyl)-2-deoxy-d-glucopyranose (di- N-acetylchitobiose) and 2-acetamido-6- O-(2-acetamido-2-deoxy- β-d-glucopyranosyl)-2-deoxy-d-glucopyranose from p-nitrophenyl 2-acetamido-2-deoxy- β-d-glucopyranoside and 2-acetamido-2-deoxy-d-glucopyranose. The ratio of the two disaccharides is time-dependent. The ratio of (1 → 4)- to (1 → 6)-isomers is a maximum (∼ 9:1) at the point of disappearance of the glycosyl donor. If left to evolve, the ratio changes to 92:8 in favour of the (1 → 6)-isomer. Either the (1 → 4)- or the (1 → 6)-isomer can be isolated by treating the appropriately enriched disaccharide mixture with the β- N-acetylhexosaminidase of Jack bean ( Canavalia ensiformis) or the β- N-acetylhexosaminidase of A. oryzae, respectively. Di- N-acetylchitobiose [GlcNAc( β1-4)GlcNAc] is an efficient donor of 2-acetamido-2-deoxy- d-glucopyranosyl units in reactions catalysed by the N-acetylhexosaminidase of A. oryzae. Di- N-acetylchitobiose itself acts as acceptor to give tri- N-acetylchitotriose [GlcNAc( β1-4)GlcNAc( β1-4)GlcNAc]. As the trisaccharide accumulates it, in turn, acts as acceptor giving tetra- N-acetylchitotetraose [GlcNAc( β1-4)GlcNAc( β1-4)GlcNAc( β1-4)GlcNAc]. The product mixture consisting of mono-, di-, tri-, and tetrasaccharides is conveniently separated by charcoal-Celite chromatography.